ITS-RFLP optimization for dermatophyte identification from clinical sources in Alagoas (Brazil) versus phenotypic methods - Luisa Andrea Villanueva da Fonseca; Maria Anilda Santos Araújo; Denise Maria Wanderlei Silva; Fernanda Cristina de Albuquerque Maranhão (Journal of Infection in Developing Countries)
Introduction: Dermatophytoses are superficial mycoses, and the identification of their etiological agents is routinely performed by culture and microscopic features, which is time-consuming and relies on personnel expertise. Molecular approaches have been developed to provide faster and reliable results; therefore, this study aimed to identify dermatophytes isolated from Alagoas state patients, employing phenotypical and molecular methods.